Gestión tributaria y la rentabilidad del sector de comidas rápidas - Montoya García, Alison Geanela (2023)
This research work is oriented to Tax Management and the profitability of the fastfood sector; In addition, the implementation of a Tax Management processes and policies model that will provide the supervision and control of the activities carried out in the accounting and tax areas, applying the benefits that the Law grants to the fast-food microenterprise sector and the correct compliance with the tax obligations, which will contribute to profitability. The first chapter presents: problem statement, problem formulation, general objective and specific objectives, research justification, idea to defend and the variables for the contribution of the fast-food microenterprise sector...........